2021
DOI: 10.1002/jmri.27553
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma With Atypical Imaging Features: Review of the Morphologic Hepatocellular Carcinoma Subtypes With Radiology‐Pathology Correlation

Abstract: Hepatocellular carcinoma (HCC) is the fastest growing cause of cancer death in the United States with the incidence rate more than doubling in 20 years. HCC is unique since a noninvasive diagnosis can be achieved with imaging alone when specific clinical criteria and imaging characteristics are met, obviating the need for tissue sampling. However, HCC is a highly heterogeneous neoplasm. Atypical HCC subtypes vary significantly in their morphology, which can be attributed to specific histologic and molecular fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 97 publications
(276 reference statements)
0
9
0
Order By: Relevance
“…Recently, Bello et al [ 74 ] brought attention to several HCC subtypes with atypical imaging features and correlated them with their histologic and molecular features; for example, an early peripheral and progressive centripetal enhancement (a pattern similar to ICC) was indicative of the scirrhous subtype. Fowler et al [ 75 ] have also presented distinct morphologic and pathologic subtypes of HCC with different prognostic implications.…”
Section: Ctmentioning
confidence: 99%
“…Recently, Bello et al [ 74 ] brought attention to several HCC subtypes with atypical imaging features and correlated them with their histologic and molecular features; for example, an early peripheral and progressive centripetal enhancement (a pattern similar to ICC) was indicative of the scirrhous subtype. Fowler et al [ 75 ] have also presented distinct morphologic and pathologic subtypes of HCC with different prognostic implications.…”
Section: Ctmentioning
confidence: 99%
“…However, HCC is a highly heterogeneous neoplasm ( 33 ). The atypical enhancement pattern may be attributed to different pathological subtypes ( 34 ). Atypical HCC subtypes vary widely in morphology, which can be attributed to specific histological and molecular features and may lead to atypical imaging features ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Atypical HCC subtypes vary widely in morphology, which can be attributed to specific histological and molecular features and may lead to atypical imaging features ( 35 ). Previous studies have shown that clear cell HCC lacks the tendency to hyperenhancement in the arterial phase and classic enhancement pattern when the proportion of clear cells was 100% ( 34 , 35 ); the most common enhancement patterns in scirrhous HCC are peripheral, rim-like enhancement and late-phase progressive central enhancement ( 34 , 35 ). In addition, Elevated AFP level has been reported to be independent predictors of MVI, which is in agreement with the present results ( 7 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, five clear cell HCC cases exhibited atypical triphasic CT features: three exhibited gradual contrast enhancement during the portal phase and two showed minimal enhancement with maintained hypoattenuation at the arterial and venous phases [42]. Therefore, awareness of the special variants of HCC may have potential clinical implications for the patients' prognosis and may serve as a diagnostic clue for the atypical imaging findings [43].…”
Section: Discussionmentioning
confidence: 99%